Recognizing The Meta-Function Of News Item - Madjdi, Achmad Hilal; Nurcahyo, Agung Dwi (Jurnal Sosial Budaya, 2014)
Language  is  a  means  of  communication  which  has  two  main  systems,  i.e.  system  of form  and  meaning.  The meanings  realized  by  language  are  textual  and  contextual  meaning.  Therefore,  language  cannot  be  separated from  its  context  of  use.  This  study  investigates  how  context  of  situation  influences  the  use  of  language,  more specifically, in the perspective of language meta-function concept. The language that is used in news items, like daily  newspaper  also  has  certain  characteristic  which  is  influenced  by  the  author  (the  writer)  and  the  socio- political situation of the society. The objective of the research is to describe how ideational meaning is realized in the Jakarta Post headline news on the fuel increasing issue. The research is a text analysis by using Systemic Functional Linguistics (SFL) theory which cover (1) the classification imbedded in the phase sequences, (2) the sequences of events in the phases, (3) The sequences of events of the Jakarta Post Headline News on fuel price- increasing issue in April 2012, which are specifically concerned with the process and (4) how people and thing are attributed in the text.